Pembuatan Sistem Informasi Manajemen Bengkel di Sekolah Menengah Kejuruan Negeri 3 Yogyakarta - Ramadhina, Syahrina (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The purpose of the study is to develop information system which can support the users in handling the management information system of Vocational High School Workshops. The study is categorized as the Educational Research Development (RD). The research procedure used in conducting this study consists of some steps i.e.: need analysis, product design, product design development, product trial/product implementation, and product evaluation. In the development phase of product design, the software was tested for feasibility by alpha validation tests and beta testing. Further product assessment to determine the performance of the system involved the users consisting of the head of the workshop, technicians, teachers, and students of Workshop at SMK 3 Yogyakarta. Data were analyzed with descriptive statistics. The result of this study was the software named Sistem Informasi Manajemen Bengkel Kerja Sekolah Menengah Kejuruan, The Management Information System of the Vocational High School Workshop (SIMBA SMK 3 Yogyakarta). Results of the assessment stated that the product had met the criteria; clear, consistent, accurate, and reliable. It was indicated by the whole score rate reaching at 3.77 in good scale.